Facilitated Participatory Orthography Development in Sorsoganon, Philippines - de la Torre, Ryan G. (Journal of the Southeast Asian Linguistics Society, 2025)
This paper describes the orthography development of the Sorsoganon language, spoken in the Bicol Region of the Philippines, using a facilitated participatory approach—a hybrid of autonomous and participatory orthography design—relevant to Southeast Asian hierarchical societies. A phonemic reanalysis of data confirmed the presence of contrastive stress and the absence of consonant-glide clusters in native Sorsoganon words, which informed the orthography's design. The influence of loanwords required the addition of eight graphemes to Sorsoganon so that it achieved a nearly one-to-one phoneme-grapheme correspondence. Spelling issues were addressed through consultations between the academic and community members, resulting in a localized orthography that slightly diverges from standard Filipino and Bikol conventions. Notable deviations include preserving natural reduplication in loanwords with consonant clusters, changing word-final to in derived forms, and substituting the first to in derived words with two consecutive medial back vowels. As Sorsoganon shows signs of evolving into a distinct language from Bikol, this study has established a consistent and standardized writing system. The orthography is recommended for use in mother tongue-based multilingual education, especially in the production of educational and literary materials to facilitate learning and adoption in the Sorsoganon-speaking community.